2021
DOI: 10.1038/s41598-021-81572-2
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotic suggestions of safety reduce neuronal signals of delay discounting

Abstract: Waiting for delayed rewards is important to reach long-term goals, yet most people prefer immediate rewards. This tendency is called delay discounting. Evidence shows that people are more willing to wait for delayed rewards when they believe that the delayed reward is certain. We hypothesized that feeling safe makes delayed outcomes subjectively more certain, which should in turn reduce neuronal signals of delay discounting. We hypnotized 24 highly suggestible participants and gave them a suggestion to feel sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 56 publications
1
13
0
3
Order By: Relevance
“…Previous studies showed that hypnotic suggestibility as measured by the HGSHS is normally distributed in the general population (Riegel et al, 2021) with individuals of low and high suggestibility comprising around 10–15% of the general population, respectively (McConkey, 2008). In analog to previous studies from our lab (Schmidt, Hoffmann et al, 2020; Schmidt & Holroyd, 2021), we only included highly suggestible participants indicated by an HGSHS score of at least 8 ( M = 8.96, SD = 0.96, range = 8–11). For participation, participants obtained either 10 Euros or course credit.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that hypnotic suggestibility as measured by the HGSHS is normally distributed in the general population (Riegel et al, 2021) with individuals of low and high suggestibility comprising around 10–15% of the general population, respectively (McConkey, 2008). In analog to previous studies from our lab (Schmidt, Hoffmann et al, 2020; Schmidt & Holroyd, 2021), we only included highly suggestible participants indicated by an HGSHS score of at least 8 ( M = 8.96, SD = 0.96, range = 8–11). For participation, participants obtained either 10 Euros or course credit.…”
Section: Methodsmentioning
confidence: 99%
“…In our lab, we developed an intervention using hypnosis to make participants feel safe. Our intervention effectively increased the subjective feeling of safety both in the EEG laboratory (Schmidt, Hoffmann, et al, 2020; Schmidt & Holroyd, 2021) and in highly stressful clinical settings such as the intensive care unit (Schmidt et al, 2021; Schmidt, Deffner, et al, 2020). In these studies, we suggested participants to feel safe using the mental image of a safe place.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People with low levels of self-control and high levels of impulsivity (i.e gambling disorders, ADHD) have difficulty in waiting for delayed rewards resulting in inability to reach long-term goals. Schmidt et al [42] hypnotized 24 participants and gave them a suggestion to feel safe, because the feeling of security may reduce the need for immediate reward. Then, they recorded the electroencephalogram to measure participants' brain responses to immediate and delayed rewards while they played a delayed gratification game.…”
Section: 4mentioning
confidence: 99%
“…In a second paradigm, I investigated another phenomenon, the devaluation of future rewards, also called delay discounting ( Schmidt and Holroyd, 2021 ). You are probably familiar with the famous marshmallow task by Mischel et al (1988) .…”
Section: Feeling Safe With Hypnosismentioning
confidence: 99%